Pelatihan Peningkatan Kewirausahaan Pada Masyarakat Kelurahan Lewaja - Ilahi, Andi Alfianto Anugrah; Arifuddin, Arifuddin; Alimuddin, Firman (Journal of Community Service and Society Empowerment, 2023)
Entrepreneurship Improvement Training in the Lewaja Village Community is a training program that aims to strengthen entrepreneurial skills among the local community. This program is designed to provide the knowledge, skills and support necessary for individuals in Lewaja Subdistrict to develop their own businesses. In this training, participants will learn important aspects of starting and managing a business, including business planning, marketing, financial management, and business development strategies. With this training, it is hoped that the people of Lewaja Village can increase their economic potential, create new jobs and contribute positively to local economic development. This program is a positive step in building community economic independence and reducing the unemployment rate in Lewaja Village.